2006
DOI: 10.1080/01496390600641611
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Contactors: Separation of an Aqueous and an Organic Stream in the Rotor Zone (LA‐UR‐05‐7800)

Abstract: A multi-phase flow code is used to simulate the separation of an aqueous and an organic stream in the rotor zone of an annular centrifugal contactor. Different values for the mixture viscosity and for the initial volume fractions of the components are considered. A simple model for mass transfer of a species between phases is used. Geometrical effects are found to have significant influence on the separation of the two-phase mixture.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…This may be due to the mixture viscosity having a maximum in the range of 1:1 phase ratio. [18] Similar trends are seen for companion liquid-liquid measurements in the lab-scale V02 contactor reported separately [16] though there are some minor differences due to changes in the vane geometry between the two contactor sizes. It was found that in the V02 CV configuration the relative liquid height was higher than 8V while for the V05 contactor this was not the case.…”
Section: Annular Liquid Heightsupporting
confidence: 68%
“…This may be due to the mixture viscosity having a maximum in the range of 1:1 phase ratio. [18] Similar trends are seen for companion liquid-liquid measurements in the lab-scale V02 contactor reported separately [16] though there are some minor differences due to changes in the vane geometry between the two contactor sizes. It was found that in the V02 CV configuration the relative liquid height was higher than 8V while for the V05 contactor this was not the case.…”
Section: Annular Liquid Heightsupporting
confidence: 68%
“…Recent research on flow conditions inside the centrifugal contactor have focused on two-phase flow but seldom addressed extraction. [50][51][52][53] Also, in the modeling of neptunium extraction, as redox reactions occur in both phases, the residence times of each phase in the phase separation zone are significant. This means the holdups of organic and aqueous in this zone must be considered in a good model of a contactor.…”
Section: Phase Separation Zone Modelmentioning
confidence: 99%
“…The formation of vertical air column along the axis of rotation of the rotor was observed and a method for the prediction of the zero-point flow rate by CFD simulation was also developed. Padial-Collins et al (2006) simulated the separation process of an aqueous and an organic stream in the rotor zone within a ACC with a size of ˚150 mm. Using multi-phase flow code under various initial and physical conditions and at different speeds of rotation, they argued that the structure size had a significant influence on two-phase separation.…”
Section: Prefacementioning
confidence: 99%